2010
DOI: 10.1371/journal.ppat.1000859
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Relationship between Infectivity and Prion Protein Aggregates Is Strain-Dependent

Abstract: Prions are unconventional infectious agents thought to be primarily composed of PrPSc, a multimeric misfolded conformer of the ubiquitously expressed host-encoded prion protein (PrPC). They cause fatal neurodegenerative diseases in both animals and humans. The disease phenotype is not uniform within species, and stable, self-propagating variations in PrPSc conformation could encode this ‘strain’ diversity. However, much remains to be learned about the physical relationship between the infectious agent and PrPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
259
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(281 citation statements)
references
References 67 publications
20
259
0
2
Order By: Relevance
“…Under these experimental conditions, PrP sedimentation profiles could be expected to reflect the size of PrP assemblies in the analyzed samples. In accordance with previous observations by Tixador et al (29), we found that the purification of PrP27-30 produced faster sedimenting PrP aggregates than observed in non-purified 263K scrapie brain homogenates (not shown). However, irrespective of this purification effect, the PrP sedimentation profiles significantly differed between the mildly and extensively sonicated preparations in that there was a substantially higher proportion of slower sedimenting (i.e.…”
Section: Ir-msp Was Not Influenced By the Size Of Prpsupporting
confidence: 93%
See 1 more Smart Citation
“…Under these experimental conditions, PrP sedimentation profiles could be expected to reflect the size of PrP assemblies in the analyzed samples. In accordance with previous observations by Tixador et al (29), we found that the purification of PrP27-30 produced faster sedimenting PrP aggregates than observed in non-purified 263K scrapie brain homogenates (not shown). However, irrespective of this purification effect, the PrP sedimentation profiles significantly differed between the mildly and extensively sonicated preparations in that there was a substantially higher proportion of slower sedimenting (i.e.…”
Section: Ir-msp Was Not Influenced By the Size Of Prpsupporting
confidence: 93%
“…Sedimentation Velocity Analysis of PrP from 263K-Brain, 263K-PMCA, and 263K-PMCA-Brain in Iodixanol GradientsIn our ultracentrifugation experiments using iodixanol gradients (29), PrP TSE from 263K-brain and 263K-PMCA-brain exhibited a higher sedimentation velocity (indicating a higher mass or a more compact shape) than PrPres from 263K-PMCA.…”
Section: Different Resistance Of 263k-brain 263k-pmca and 263k-pmcamentioning
confidence: 78%
“…This infectivity was approximately 50-fold higher in the case of the139H strain. 17 Taken together, the above data indicate that the aggregation state or quaternary structure of PrP Sc is relevant for prion infectivity. Furthermore, it is very likely that additional conformational aspects, such as those derived from the tertiary structure, play an important role in determining the differential infectivity of specific prion strains.…”
Section: Prions Proteinase K and Infectivitymentioning
confidence: 73%
“…The authors did not interpret the results as an aggregation size difference but as a difference in its tertiary structure. 17 Finally, PK-sensitivity appears to be connected with oligomer stability which in turn is directly proportional to the incubation time. Colby and coworkers demonstrated that stable recombinant OC antibody (which recognizes amyloid fibrils but not monomers or soluble prefibrillar oligomers).…”
Section: Pk Sensitive Prp Scmentioning
confidence: 99%
“…Les analyses par spectrométrie infrarouge indiquent que la PrP Sc est fortement enrichie en feuillets b (~40 % contre 3 % pour la PrP C ). Un certain nombre (Silveira et al, 2005, Tixador et al, 2010. Des études ultra structurales par microscopie électronique à transmission ou par microscopie à force atomique de fractions semi-purifiées de PrP Sc ont également permis la visualisation de structures fibrillaires de taille variable (10 à 100 nm de long, 5 nm de large, (Sim & Caughey, 2009) Sc est dépendante à la fois de leur taille et de la souche considérée (Tixador et al, 2010, Laferriere et al, 2013.…”
Section: Polydispersite Des Particules Prion Et Activité Biologiqueunclassified